Estimating tomato production losses due to plant viruses, a look at the past and new challenges - Sánchez-Sánchez, Mario; Aispuro-Hernandez, Emmanuel; Quintana-Obregon, Eber Addi; Vargas-Arispuro, Irasema del Carmen; Martinez-Tellez, Miguel Angel (Comunicata Scientiae, 2024)
This review analyzes the available technical and scientific reports addressing tomato crop losses and discusses the ponderable characteristics for estimating losses caused by Tomato Infecting-Viruses. The tomato around the world represents an important economic aspect, it has positioned as a crop that contributes to the gross domestic product and is essential to achieve food security in some regions. Viral diseases are one of the main causes of economic losses and tomato production, due to the easy dissemination of viral particles, difficult detection, and the few options to combat virus diseases. Tomato Infecting-Viruses such as ToBRFV, TLYCV, TSWV, and TMV are some of the most important viruses due to their ability to cause losses. Abiotic factors must be considered to estimate losses with greater precision and biotic factors, restricted mainly to insects, have an important role in the virus dispersion and adaptation to new niches not studied yet. Viral infections in tomato crops can reach 100% and reported losses are between 2 and 10%. There are no recent official statistics on economic losses due to tomato viruses, the main limitation is to extrapolate and accurately predict today's losses with data from the past decade. The main challenges for estimating the economic impact of viral diseases in tomato crops lie in the omission by growers and authorities on the presence of viral symptoms and the product value in the market. Considering the absolute value of tomato cultivation economic losses by virus diseases should be around 2 to 5% annually.